The effect of utilization of Licorice extract on milk ylied and its chemical composition in black local dose - Al- musodi, Mohaned F. H. (Journal of Kerbala for Agricultural Sciences, 2018)
The aim of this study was investigate the effect of the licorice extract on milk production and chemical composition in local black dose its conducted in private farm in Karbala ,fifteen does in forth month gestation period were randomly adivided into three groups (5 each) animal of first group (control ) free of any addition only concentrated diet, the 2nd group (T1) feeded on 250 mg. of licorice weekly / kg body weight as food addivites , while the 3rd group (T2) feed on350 mg of licorice weekly / kg body weight as afood addivites , weekly milk yield and milk chemical composition (fat %,protein %, lactose% and soild non fat (snf)% ) was investigated milk yield checked for 6 week and samples of milk were taken for laboratory analysis , the result showed asignificant increase (P< 0.05) in milk fat% in 2nd group(T1) and 3rd group (T2) compared with the control group (C ) no significant difference were abserved in milk ylied, milk protein %, lactose %and Snf % between all groups.